Corpoica H5: the first high quality protein (QPM) hybrid maize for Colombian eastern plains (2014)
Colombia has an annual deficit of maize to meet the feed industry. In 2012, the country produced only 20.2% of the corn required by the industry; 1.0% of this production is obtained on the Colombian high plains (20,000 hectares); however, this region has an area of 500,000 hectares suitable for growing corn. To meet domestic demand, the government implemented the National Maize Plan (Plan País Maíz): a promoting and research strategy to assess and identify hybrids with yield and quality attributes that allow the competitiveness of this crop. In this context the present research was conducted, which identified the maize hybrid H5, with the following characteristics: high quality protein; grain yield of 5.05 t/ha, statistically similar to that obtained with commercial controls; male and female flowering of 56 and 57 days; period from planting to harvest of 112 days; plant height and cob of 185 and 94 cm,respectively; resistance to stem and root tumble, and to Cercospora sp. and Phaeosphaeria sp. Hybrid H5 showed per 100 g of protein, 4.10 g of lysine and 0.87 g of tryptophan; these values were higher by 1.7 and 2.0 times than those obtained by conventional maize (P30K73) having 2.32 g of lysine and 0.43 g of tryptophan. These characteristics of crystalline grain texture and high quality protein confer it commercial recommendation, because it is appropriate for the feed industry.